The influence of planting size and configuration on landscape fire risk. (15th October 2019) - Jenkins, Meaghan; Price, Owen; Collins, Luke; Penman, Trent; Bradstock, Ross
Abstract: Revegetating cleared land with native trees and shrubs is increasingly used as a means of addressing loss of biodiversity, degraded soil and water resources and sequestration of carbon. However, revegetation also brings a potential to alter fire risk due to changing fuel types across the landscape. Previous research has found that increasing the area of revegetation does not increase the risk of fire at a landscape scale, but it remains unclear whether the design of revegetation can be optimised to minimise risk. We evaluated if size and arrangement of revegetation affects fire size and intensity within an agricultural setting using a simulation modelling approach. Three revegetation planting designs were assessed, including small (3.2 ha) dispersed plantings, small (3.2 ha) plantings clustered into one third of the landscape, and large (29.2 ha) dispersed plantings, all resulting in the same overall percentage of revegetation (approximately 10% of the landscape). We simulated fires using Phoenix Rapidfire under varying planting design, weather, surrounding pasture conditions, and fire suppression. Planting design had little effect on fire sizes across the landscape, with larger plantings resulting in slightly larger fire sizes. Fires were smaller in landscapes with all planting designs compared with current landscape patterns. There was no significant influence of planting design on fire intensity. Weather and suppression had the strongest influence on both fire size and intensity, with larger and more intense fires under extreme weather conditions, with higher adjacent pasture loads and with no simulated suppression. Management of fuel loads in the pasture surrounding revegetation, weather and suppression are far greater risk factors for fire in these landscapes than planting design. Highlights: Planting design had little effect on fire sizes across the landscape. Planting design had no significant influence on fire intensity. Weather, suppression and adjacent pasture fuel load are greater risk factors.